The integration of scaffolding and augmented reality in physics learning - Karim, Siti Nurqualbiah Mat; Karim, Aidah Abdul; Khalid, Fariza (International Journal of Evaluation and Research in Education (IJERE), 2025)
Physics learning often involves problem-solving in mathematical calculation that has become one of the many challenges among high school students. The integration of scaffolding and augmented reality (AR) has the potential to improve students’ understanding in problem-solving involving mathematical calculation in physics learning. Therefore, this study aims to increase gravitational knowledge among high school students using AR learning kit with the integration of scaffolding. This study employed mixed method case study research design and involved 15 high school students in urban areas. Data was collected using semi structured interview and pre and post gravitation test then analyzed using qualitative thematic analytic and descriptive statistics. The findings showed that an AR learning kit integrating scaffolding named FizaAR has increased gravitational knowledge among high school students in physics learning. The findings further indicated that scaffolding element employed in FizaAR have the feature of simplified small subtopics help to increase confidence among students in physics learning. Consequently, the AR learning kit might enhance high school students’ understanding of physics. This study found that integrating scaffolding and AR would help physics education.